Upregulation of cyclin‐dependent kinase 7 and matrix metalloproteinase‐14 expression contribute to metastatic properties of gastric cancer. Issue 10 (25th August 2016) - Naseh, Ghodratolah; Mohammadifard, Mahyar; Mohammadifard, Mahtab
Abstract: The aim of this study was to evaluate the protein and mRNA expressions of matrix metalloproteinase‐14 (MMP14) and CDK7 in gastric cancer (GC) tissues. Upregulation of MMP14 mRNA level was observed in GC tissues when compared with the matched normal tissues (mean ± SD: 3.92 ± 1.15 vs. 1.35 ± 0.81, P < 0.001). This study indicated that mRNA levels of CDK7 were statistically overexpressed in GC when compared with matched normal tissues (4.12 ± 0.84 vs. 1.43 ± 0.71, P < 0.001). The protein levels of MMP14 were found to be increased in GC (60.41%; P < 0.001). The expression of CDK7 was higher in GC tissues than matched normal tissues (70.83; P < 0.001). We found that high MMP14 expression was related to advanced TNM stage ( P = 0.004), tumor grade ( P = 0.002), and lymph node metastasis ( P = 0.015), but no association with other clinical variables ( P > 0.05). In addition, high expression of CDK7 was significantly linked to advanced TNM stage ( P = 0.001), pathological grade ( P = 0.012), and presence of lymph node metastasis ( P = 0.009), while no correlation between CDK7 expression and other clinical variables, such as age and gender, distance metastasis. The patients with high expression of MMP14 and CDK7 exhibited worse survival time than those with higher levels. Cox multivariate regression analysis clearly showed that high expression of MMP14 and CDK7 was independent prognostic factors for overall survival in patients with GC. Taken together, these results indicated the overexpression of above markers in the progression and the tumorigenesis of GC and overall patient survival. © 2016 IUBMB Life, 68(10):799–805, 2016